(untitled) (Práxis Educativa, 2010)
The present article analyzes the coexistence of the Escola Guaicuru – Vivendo Uma Nova Lição Program and the Secondary School Improvement and Expansion Program (Promed/Escola Jovem) during the years 1999 to 2006. It emphasizes that, according to the Law nº. 9.424/1996 (Fundef), the state is responsible for transferring financial resources to its municipalities. As a result, the state government had to seek new sources of funding for the Secondary Education, such as the Promed, proposed and coordinated by the Ministry of Education and Culture - MEC. The research was based on the educational legislation, on federal and state government documents and on the relevant literature. It concluded that the coexistence of the Escola Guaicuru – Vivendo uma Nova Lição Program and the Promed distorted the assumptions of the state educational policy because the programs themselves had different orientations. As the state did not fully comply with the goals of the Promed, it could not receive the necessary resources to invest in the secondary school. Keywords: Educational Policy. Secondary School. Education Funding.